Combination Between Design for Assembly and Design for Serviceability Method in Concurrent Engineering: A Literature Review - Akbar Gading Alfadli Harahap; Rosnani Ginting; Aulia Ishak (TALENTA Publisher, 2026)
Increased competition in the industry encourages companies to focus on customer satisfaction to maintain competitiveness. The combination of Design for Assembly (DFA) and Design for Serviceability (DFS) methods is a common concern for researchers, especially in product development. This research describes the integration of DFA and DFS methods to solve product problems, starting from the method development stage, the interrelationship between the two methods, etc. The successful application of these methods is evident through high efficiency and improved product quality. Key factors involved management cooperation, use of quality tools, and teamwork. Leading journals highlight product cost reduction through Design for Serviceability and DFA techniques. Emphasis on sustainability, especially by integrating sustainability goals in product design, evidenced positive environmental impact and market response. Research also highlighted the need for identification and prioritisation of customer requirements and optimisation of production process parameters. The integration of modelling methods and design systems, such as in the development of a modelling system for metal casting processes, demonstrated success in achieving effective product development goals. Overall, this research provides an in-depth understanding of the potential and benefits of applying DFA and DFS in efficient, high-quality and sustainable product development, providing a foundation for further development and implementation by practitioners and researchers.